Habitat edge responses of generalist predators are predicted by prey and structural resources. Issue 6 (23rd April 2019) - Wimp, Gina M.; Ries, Leslie; Lewis, Danny; Murphy, Shannon M.
Abstract: Generalist predators are thought to be less vulnerable to habitat fragmentation because they use diverse resources across larger spatial scales than specialist predators. Thus, it has been suggested that generalist predators may respond positively to habitat edges or demonstrate no edge response, because they can potentially use prey resources equally well on both sides of the habitat edge. However, most predictions about generalist predator responses to the habitat edge are based solely on prey resources, without consideration of other potential drivers. For instance, structural resources are essential for some species to build webs to capture prey or to avoid intraguild predation and cannibalism. In this study, we used both prey and structural resources to predict the response of four predator functional groups (hunting spiders, web‐building spiders, aerial predators, and epigeic predators that feed on the detrital/algal food web) to a habitat edge between two salt‐marsh grasses ( Spartina alterniflora and Spartina patens ). We found that generalist predators largely demonstrated negative responses to the habitat edge and had distinct habitat associations. Positive edge responses were only observed in one functional group (hunting spiders), and this pattern was driven by the two most abundant species. Negative responses to the habitat edge were more common among taxa and were better explained by structural resources rather than prey resources in the two habitats. Although it is generally acknowledged that specialists decline in fragmented habitats, generalists are thought to be more resilient. However, our research demonstrates that even generalists have habitat structural or food resource requirements that may limit their resilience to habitat loss and fragmentation.